Hyperechogenic Bowel: Etiologies, Management, and Outcome according to Gestational Age at Diagnosis in 279 Consecutive Cases in a Single Center - Catania, Vincenzo Davide; Taddei, Alessandra; Pellegrino, Marcella; De Marco, Erika Adalgisa; Merli, Laura; Manzoni, Carlo; Nanni, Lorenzo; Masini, Lucia (European Journal of Pediatric Surgery, 2017)
Introduction The aim of the study was to investigate perinatal outcome of fetuses with hyperechogenic bowel (HB) in relation to gestational age at diagnosis.Materials and Methods This is a retrospective observational study of fetal HB cases from 2002 to 2012. Patients were divided into three groups according to trimester at diagnosis. For each group, data from fetal ultrasound examination, fetal medicine investigations, intrapartum cares, and neonatal outcome were obtained.Results A diagnosis of HB was made in 279 fetuses among them 17 (6%) during the first trimester, 186 (67%) during the second trimester, and 75 (27%) during the third trimester. A significant prevalence of maternal comorbidities was noticed in group 1 (12%: p = 0.02). A chromosomal defect was identified in 13% of the fetuses without difference among the three groups. HB was associated with prenatal infection in 11.5% (n = 32) of the cases, with an equal distribution between groups 2 and 3. Intrauterine growth retardation was noticed in 23% (n = 64) of the cases with a slightly high prevalence in groups 1 (35%). HB was the only ultrasonographic intestinal soft marker in 80% (n = 223) of the fetuses, two-third of them were detected during the first and the second trimesters (p = 0.001). However, HB was associated with bowel dilation in 33% of the cases diagnosed during the third trimester (p = 001). Ultrasonographic extraintestinal anomalies were identified in 30% of the fetuses with a higher prevalence in group 1 (59%). HB resolved spontaneously in 55 (19.7%) cases—without difference among the three groups. In group 1 we recorded a significant prevalence of intrauterine demise (23.5%, p = 0.004). Two hundred twenty-seven (81.3%) pregnancies resulted in live-born neonates; among them gastrointestinal anomalies were noticed in 12.5% with a significant prevalence in group 3 (36%) compared with 6 and 5.4% in groups 1 and 2, respectively (p = 0.001). Extraintestinal anomalies were confirmed in 27% of the cases, whereas postnatal mortality rate was of 7% without differences between the three groups.Conclusion Detection of HB during the first trimester is associated with an increased risk for maternal comorbidities, intrauterine growth retardation, and adverse pregnancy outcome. Moreover, if HB is detected during the second trimester, it is associated with a favorable prognosis. Otherwise, HB detected during the third trimester is associated with a significant risk of gastrointestinal anomaly.
Keywords: hyperechogenic bowel; gestational age; outcome; intestinal malformation